2019
DOI: 10.18502/ijm.v11i1.697
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Listeria monocytogenes from environmental and clinical sources by culture and PCR-RFLP methods

Abstract: Background and Objectives: Due to the widespread distribution of Listeria monocytogenes in environmental and animal sources and serious clinical complications in human, this study was aimed to isolate L. monocytogenes from water and clin- ical specimens by culture and PCR methods and to investigate the presence of hlyA and inlA virulence genes. Materials and Methods: Water and clinical samples of vaginal and fecal were screened for the presence of L. monocyto- genes by phenotypic and standard biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Confirmation of bacterial spp. for E. coli O157, Salmonella L. monocytogenes , and Campylobacter was performed using a multiplex-PCR assay (mPCR) [ 39 , 42 , 43 , 44 ]. PCR products were visualized using gel-electrophoresis on a 2% agarose gel containing 0.5 µg/mL ethidium bromide.…”
Section: Methodsmentioning
confidence: 99%
“…Confirmation of bacterial spp. for E. coli O157, Salmonella L. monocytogenes , and Campylobacter was performed using a multiplex-PCR assay (mPCR) [ 39 , 42 , 43 , 44 ]. PCR products were visualized using gel-electrophoresis on a 2% agarose gel containing 0.5 µg/mL ethidium bromide.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study conducted by Mpondo (2021), it was found that L. monocytogenes was present in 13% (9/69) of water samples collected from river and irrigation waters in the Eastern Cape Province of South Africa. Previously, Meghdadi et al (2019) also detected L. monocytogenes 16.76% (16/180) in river waters. The high prevalence of L. monocytogenes in the river is likely due to anthropogenic inputs (Khatri and Tyagi, 2014).…”
Section: Resultsmentioning
confidence: 79%
“…Furthermore, the inlA gene, one of L. monocytogenes virulence genes, can be used as a marker for the detection of L. monocytogenes in water and agricultural produce. The inlA gene was recently used for the identification of L. monocytogenes isolated from clinical sources, including vaginal swabs and faeces (Meghdadi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nuclease-Free Water was added according to the nmol concentration. Using a 1.5 mL Eppendorf tube, 5 μL of the R primer were added, and it was then filled up with 45 μL of Nuclease-Free Water, resulting in a total solution of 50 μL that recognizes the genus Listeria monocytogenes in 388 bp (15) .…”
Section: Sample Preparation For Listeria Monocytogenesmentioning
confidence: 99%